Ex Vitro Establishment of Jack (Artocarpus heterophyllus Lam.) Plantlets - Ramesh B (Department of Horticulture, College Of Agriculture, 1990)
The problem of poor ex vitro establishment of jack plantlets was addressed in a study conducted during 1988-90 at the Plant Tissue Culture Laboratory of the Department of Horticulture, College of Agriculture, Vellayani. A reliable protocol could be standardized based on the analysis of the factors influencing plantlet production and their ex vitro establishment and characterization of the morphological, histological and physiological peculiarities of the in vitro raised plantlets.